(untitled) (Global Scientific Review, 2023)
This article talks about the use of new pedagogical technologies in teaching English. The article talks about the importance of using new pedagogical technologies in the teaching of English, and all the possibilities of the student are analyzed, taking into account the complexity of mastering the subject. Also, examples of new methods in language development are given and its importance is revealed.